2023
DOI: 10.1093/jxb/erad374
|View full text |Cite
|
Sign up to set email alerts
|

The leaf idioblastome of the medicinal plantCatharanthus roseusis associated with stress resistance and alkaloid metabolism

Joana G Guedes,
Rogério Ribeiro,
Inês Carqueijeiro
et al.

Abstract: Catharanthus roseus leaves produce a range of monoterpenoid indole alkaloids (MIAs) that include low levels of the anticancer drugs vinblastine and vincristine. The MIA pathway displays a complex architecture spanning different subcellular and cell-type localizations and is under complex regulation. As a result, the development of strategies to increase the levels of the anticancer MIAs has remained elusive. The pathway involves mesophyll specialised idioblasts where the late unsolved biosynthetic steps are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…4). While candidate TFs can be identified from gene expression data alone 8,35 , we demonstrated that cell-type specific chromatin accessibility profiles allowed us to identify putative cell-type specific cisregulatory elements and the corresponding TF families using motif enrichment (Fig. 4C, Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…4). While candidate TFs can be identified from gene expression data alone 8,35 , we demonstrated that cell-type specific chromatin accessibility profiles allowed us to identify putative cell-type specific cisregulatory elements and the corresponding TF families using motif enrichment (Fig. 4C, Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Since the entire vinblastine biosynthetic pathway is elicited by methyl-jasmonate 17,18 , the MeJA-responsiveness displayed by these TF candidates suggests they might be transcriptional activators of the pathway. A recent study applied fluorescence activated cell sorting to enrich for idioblast cells prior to RNA-seq 35 . Consistent with their idioblast specificity, all four TF candidates were detected at high levels in the idioblast fraction of sorted cells, but not in the mesophyll fraction (Supplementary Fig.…”
mentioning
confidence: 99%
“…MIAs are biosynthesized through the collaboration of four cell types, namely internal phloem‐associated parenchyma (IPAP) cells, epidermal cells, idioblasts, and laticifers (Fig. 1), with the final products, and intermediate accumulating in the latter two (St‐Pierre et al ., 1999; Miettinen et al ., 2014; Yamamoto et al ., 2016, 2019; Sun et al ., 2022; Li et al ., 2023; Guedes et al ., 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Upon cell damages caused by insect attack, catharanthine and vindoline converge, facilitating enzymatic condensation to form the dimeric vincristine and vinblastine (Roepke et al, 2010). Recent single cell metabolome analyses have indicated that catharanthine and vindoline co-localize in idioblast and laticifer cells (Guedes et al, 2024; Li et al, 2023; Yamamoto et al, 2019; Yamamoto et al, 2016). Despite their co-localization, the concentrations of the dimeric compounds remain low, raising another possibility that the enzymes responsible for dimerization are localized in cell types other than idioblast and laticifer.…”
Section: Introductionmentioning
confidence: 99%